FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PERUSAHAAN MANUFAKTUR - NOVA DWI HANDAYANI; NICKEN DESTRIANA (E-Jurnal Akuntansi TSM, 2021)
The objective of this research is to obtain empirical evidence about the influence of sales growth, earnings per share, book to market value, market capitalization, current ratio, total asset turnover, debt to equity ratio, and return on asset on stock return. This reasearch used manufacturing companies that listed in Indonesia Stock Exchange from 2013-2015, and 55 companies selected as final sample and acquired 163 observational data as the sample. Sampling method in this research was purposive sampling. The analysis technique used is multiple regression analysis. The result of this research shows that sales growth, book to market value, and return on asset have effect to stock return. Meanwhile the other variables such as earnings per share, market capitalization, current ratio, total asset turnover, and debt to equity ratio don’t have any effects to stock return.